Preferensi Konsumsi Dalam Islam: Telaah atas Konsep Maslahah pada Perilaku Konsumsi - Unun Roudlotul Janah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2008)
This study aims to analyze consumption preferences in Islam by examining the concept of maslahah (public interest) as a normative basis for consumption behavior. Using a qualitative method through a literature study approach, this study examines classical and contemporary Islamic economic literature, as well as the principles of Islamic maqashid (objectives of Islamic law) related to consumptive behavior. The results show that consumption in Islam is not only based on personal satisfaction, but must also consider individual and collective benefits (maslahah), as well as the values of justice, balance, and sustainability. The concept of maslahah limits excessive consumption and encourages an ethical and responsible consumption orientation. This study emphasizes that consumption preferences in Islam are holistic, combining spiritual, social, and economic aspects for the realization of equitable welfare.